Parola e tecnica. L’eclissi del linguaggio come eclissi dell’umano - Palma, Enrico (Mechane, 2024)
The essay attempts to articulate a reflection on the language-technique relationship, focusing in particular on the negative influence that technique determines on the linguistic essence of human. Our premise is that current times are an era of cultural and spiritual decline, as this linguistic essence is increasingly lacking. To discuss causes, origins and possible escape routes from this trap, here we try to decline a free dialogue with Heidegger’s later work, mostly following this argumentation: the concealment of essence of entity carried out by technique; the relationship between word, technique and unveiling; the re-appropriation of entity and lost essence of human through an idea of science and knowledge that is absolutely not subjugated by contemporary technical deployment, which knows how to redeem language and listen to it again.